2014
DOI: 10.1249/mss.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Exercise on Clinically Measured Reaction Time in Collegiate Athletes

Abstract: Purpose We have developed a reliable and valid clinical test of reaction time (RTclin) that is sensitive to the acute effects of concussion. If RTclin is to be used as a sideline concussion assessment tool then the acute effects of exercise on RTclin may need to be controlled for. The purpose of this study is therefore to determine the effect of exercise on RTclin. Methods A gender balanced group of 42 collegiate athletes were assigned to an exercise (n=28) and a control (n=14) group using 2:1 block randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
6
2
Order By: Relevance
“…There exists significance difference, p < 0.001 between them. MCRT among the young college male is greater than reported by Reddy et al 4 (214 ± 18 ms) and Eckner et al 5 (247 ± 75 ms) in college athletes. This difference might attribute to the regular training session by the athletes.…”
contrasting
confidence: 50%
“…There exists significance difference, p < 0.001 between them. MCRT among the young college male is greater than reported by Reddy et al 4 (214 ± 18 ms) and Eckner et al 5 (247 ± 75 ms) in college athletes. This difference might attribute to the regular training session by the athletes.…”
contrasting
confidence: 50%
“…Practice effects (ie, faster responses) for RTclin were noted over a 5-week period, with the most pronounced improvement in reaction time occurring between the first two trials47. A third study53 found no association between exercise and reaction time, although a practice effect was found for both the experimental exercise group and the non-exercising controls. Additionally, females had slower reaction time than males.…”
Section: Resultsmentioning
confidence: 93%
“…‡Slower than football and boys' soccer players in 2011; P , 0.001. before a workout, and some would present after a workout. Some studies in the literature have found a differential effect of exercise on reaction time, 29,30 although a recent study by Reddy et al 31 showed that RT clin itself was not affected by recent exercise. In addition, there were some student-athletes in both years who were not baseline tested simply because they did not show up on test day.…”
Section: Discussionmentioning
confidence: 99%